Factors Associated with Post-Natal Care Utilization among the Women of Reproductive age Group: Evidence from Bangladesh Demographic and Health Survey 2017-18 - Israt Tahira Sheba; Abdur Razzaque Sarker; Afrida Tasnim (SAGE Publishing, 2022)
Introduction Postnatal period is a crucial stage of illness for mothers and their newborn children. Lack of post-natal care (PNC) services during this period is lifethreatening for both the mother and the babies. This study aims at examining the associated factors of PNC utilization among the mothers to explore the opportunities to accelerate it. Methods This study utilized the latest data from Bangladesh Demographic and Health Survey (BDHS) 2017-18, a nationally representative survey. A weighted sample of 5043 Bangladeshi women who gave birth three years prior to the survey was studied. Bivariate and multivariate analyses were performed to identify the underlying factors associated with the utilization of PNC. Results Around 63% women sought PNC from any kind of provider within 24 h to 42 days of the delivery among whom more than 48% received it from medically trained providers. Together with several sociodemographic factors- administrative division, place of residence, educational level, employment status, wealth status, some maternal factors such as- antenatal care (ANC) visits, place and mode of delivery- played a significant role in utilizing PNC services from trained providers. Conclusion To further improve utilization of post-natal care, national and local level action plans should be introduced to promote health facility delivery irrespective of their place of residence. In the meantime, PNC awareness campaigns, intervention and economic empowerment programs targeting mothers from the poorest quintile needs to be implemented, particularly those who are unable to attend at least four ANC visits, and have accessibility issues to education.